PENGARUH PERGAULAN ISLAMI TERHADAP PEMBENTUKAN KEPRIBADIAN RELIGIUS REMAJA: Studi di Pondok Pesantren Al-Ishlah Bobos Cirebon - Dinda Nurazijah; Adang Darmawan Achmad; Muhammad Aziz Husnarrijal (Jurnal An-Nufus, 2022)
Islamic socialization is an interaction between one Muslim and another Muslim in daily life in accordance with Islamic values and teachings implemented in various fields, one of which is socialization in educational institutions. In the educational environment, religious values and teachings are usually used as a reference in making rules that are enforced; the hope is that it can be a motivation to always behave well in everyday life. This research discusses the extent of the influence of Islamic socialization on the formation of the religious personality of adolescents at the Al-Ishlah Bobos Cirebon Islamic Boarding School. The purpose of this study is to determine the true meaning of Islamic association and prove the extent of the influence of Islamic association on the formation of a religious personality. The population in this study was 113 students. The researchers took a sample of 43%, so the overall sample was 48 students of Al-Ishlah Islamic Boarding School. the research method uses a quantitative type with a correlation approach based on data obtained in the field with data collection through distributing questionnaires, observation, and documentation. Data analysis using the help of SPSS version 17.0. This study got an effective contribution R2 = 0.22 which shows that 22% of religious personality variables are influenced by Islamic association.